2022
DOI: 10.1111/exd.14639
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome and melanoma: A review

Abstract: Disturbances in the microbial ecosystem have been implemented in chronic inflammation, immune evasion and carcinogenesis, with certain microbes associated with the development of specific cancers. In recent times, the gut microbiome has been recognised as a potential novel player in the pathogenesis and treatment of malignant melanoma. It has been shown that the composition of gut microbiota in early‐stage melanoma changes from in situ to invasive and then to metastatic disease. The gut bacterial and fungal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…16 Factors well-established for increasing the risk of melanoma development include UV radiation and familial history of melanoma. 16 Recently, gastrointestinal microbiota has been recognized as a novel environmental factor contributing to both the pathogenesis of melanoma development and its influences on therapeutic outcomes. 16 Although the exact relationship between gut dysbiosis and melanoma is still being explored, multiple studies have yielded evidence for their interplay.…”
Section: Role Of Gut and Skin Microbiome In Immunotherapy Of Melanomamentioning
confidence: 99%
See 2 more Smart Citations
“…16 Factors well-established for increasing the risk of melanoma development include UV radiation and familial history of melanoma. 16 Recently, gastrointestinal microbiota has been recognized as a novel environmental factor contributing to both the pathogenesis of melanoma development and its influences on therapeutic outcomes. 16 Although the exact relationship between gut dysbiosis and melanoma is still being explored, multiple studies have yielded evidence for their interplay.…”
Section: Role Of Gut and Skin Microbiome In Immunotherapy Of Melanomamentioning
confidence: 99%
“…16 Recently, gastrointestinal microbiota has been recognized as a novel environmental factor contributing to both the pathogenesis of melanoma development and its influences on therapeutic outcomes. 16 Although the exact relationship between gut dysbiosis and melanoma is still being explored, multiple studies have yielded evidence for their interplay. Vitali et al 17 found that bacterial and fungal gut profiles differed drastically between melanoma and control cohorts.…”
Section: Role Of Gut and Skin Microbiome In Immunotherapy Of Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical data shows that radiotherapy can aggregate antitumor T cells and increase the sensitivity of refractory tumors to immune checkpoint inhibitors [ 153 ]. Recent studies on ICI therapies have shown that the changed gut microbiota may affect the antitumor immunity of tumor patients, thereby affecting the resistance to ICI, while the supplementation of different types of bacteria can restore the response to anticancer drugs [ 154 , 155 ]. It is worth mentioning that the gut microbiota can modulate antitumor immunity through small-molecule metabolites, which can disseminate from their original location in the gut to the whole body, influencing local and systemic antitumor immune responses and promoting the efficiency of ICI [ 146 ].…”
Section: Interactions Between Gut Microbiota and Radiotherapymentioning
confidence: 99%
“…Changes in gut microbiota from early stages to metastatic disease were described by Vitali et al, who observed an abundance of Prevotella copri and yeasts of the Saccharomycetales species in melanoma patients compared to controls [ 68 ]. A review recently published by Makaranka et al managed to describe the current evidence regarding the carcinogenic and anti-tumoral properties of GM in melanoma, emphasizing its connection with response to radiotherapy, chemotherapy and ICI and the impact that diet and probiotics may have in this scenario [ 69 ]. As an example, GM has been reported to trigger the immune system to strengthen the abscopal effect caused by radiotherapy, apart from promoting radiotherapy-adverse effects such as mucositis, colitis and bone marrow failure [ 70 ].…”
Section: Gut Microbiome and Cancermentioning
confidence: 99%